Factors Affecting Hospital Length of Stay following Total Knee Replacement: A Retrospective Analysis in a Regional Hospital - Scholes, Corey; Cowley, MacDougal; Ebrahimi, Milad; Genon, Michel; Martin, Samuel J. (The Journal of Knee Surgery, 2019)
In an effort to reduce hospital length of stay (LoS) following total knee arthroplasty (TKA), patient management strategies have evolved over time. The aims of this study were threefold: first, to quantify the reduction in LoS for TKA in a regional hospital; second, to identify the patient, surgical and management factors associated with hospital LoS; and lastly, to assess the change in complications incidence and hospital readmission as a function of LoS. A retrospective chart review was conducted on a consecutive series of primary and revision TKAs from January 2012 to March 2018. Factors describing patient demographics, as well as preoperative, intraoperative, surgical, and postoperative management, were extracted from paper and electronic medical records by a team of reviewers. Multivariate linear regression was performed to assess the association between these factors and LoS. In total, 362 procedures were included, which were reduced to 329 admissions once simultaneous bilateral procedures were taken into account. Median LoS reduced significantly (p = 0.001) from 6 to 2 days over the period of review. A stepwise regression analysis identified patient characteristics (age, gender, comorbidities, discharge barriers), perioperative management (anesthesia type), surgical characteristics (approach, alignment method), and postoperative management (mobilization timing, postoperative narcotic use, complication prior to discharge) as factors explaining 58.3% of the variance in LoS. Representation to emergency (6%) and hospital readmission (3%) remained low for the reviewed period. Efforts to reduce hospital LoS following TKA within a regional hospital setting can be achieved over time without significant increases in the rate or severity of complications or representation to acute care and subsequent readmission. The findings establish the role of patient, surgical and management factors in the context of agreed discharge criteria between care providers.
Keywords: enhanced recovery; total knee arthroplasty; length of stay; complications; regional hospital; stepwise regression